Determination of Fe(II) in Drinking Water by Paper-Based Microfluidic Devices with Colorimetric Sensing - Ninwong1, B.; Dungchai2, W. (Asian Journal of Chemistry, 2014)
A colorimetric method has been developed for determination of Fe(II) by paper-based microfluidic devices (μPADs). The analytical device is easily constructed using wax-printing on filter paper with was indicated that hydrophobic zone. Fe(II) was detected by the reaction of Fe(II) and 1,10-phenanthroline which the red/orange ferroin complex [Fe(phen)3]2+ was formed. Under the optimum conditions, the linear range between the color intensity and the concentration were found to be 0.1-3.5 and 3.5-15 mg L-1, but with a different slope. The limits of detection were obtained at the concentrations as low as 0.07 mg L-1. The proposed method can be successfully applied to the determination of Fe(II) in drinking water sample. The recoveries were in the range 86.60-109.80 %. The present procedure provides rapid, sensitive and selective for detection of Fe(II), minimal reagent consumption, low cost, thus it is suitable for on-site environmental monitoring.